From pentecost to Patmos : an introduction to Acts through Revelation - Blomberg, Craig L., 1955- (USA : B & H Academic, 2006)
From Pentecost to Patmos is professor Craig L. Blomberg's follow-up companion to his 1998 ECPA Gold Medallion Award-winning book, Jesus and the Gospels. In the same style as that first acclaimed and widely used volume, the author goes deep into the biblical writings of Acts through Revelation, helping serious Bible students to better understand the historical, linguistic, and theological significances found in each book. --
Pt. 1: Acts of the apostles -- Acts: the Gospel moves out -- Pt. 2: Paul and his letters -- Paul: life and ministry -- Galatians: the charter of Christian liberty -- The Thessalonian correspondence: a balanced view of Christ's return -- The Corinthian correspondence: countering misguided views about Christian maturity -- Romans; the most systematic exposition of Paul's Gospel -- The prison epistles: general introduction -- The pastoral epistles: general introduction -- Pt. 3: Other New Testament writings -- The Epistle of James: "Faith without works is dead" -- The Epistle to the Hebrews: the superiority of Christ -- 1 Peter: perseverance despite persecution -- The Epistle of Jude: "Contend for the faith" -- 2 Peter: "Where is the promise of His coming?" -- The epistles of John: the tests of life -- The Book of Revelation: God's plans for cosmic history
Includes bibliographical references and index
Keywords: Bible. -- Introductions; Bible. -- Introductions; Bible. -- Introductions